Perbaikan Lingkungan Kerja Menggunakan Metode 5S (Seiri, Seiton, Seiso, Seiketsu, dan Shitsuke) di Bengkel Senior Motor - Umaisyah, Umaisyah; Uslianti, Silvia; Wijayanto, Dedi; Putri, Famelga Clea; Prawatya, Yopa Eka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Senior Motor Workshop faced several workplace problems, including disorganized working areas, untidy equipment, low cleanliness levels, and the absence of Standard Operating Procedures (SOPs). This study aims to improve the workplace environment through the implementation of the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) and to develop SOPs as guidelines for sustainable implementation. Data were collected through observation, interviews, and documentation, covering workshop conditions, workspace and rack dimensions, layout, as well as the quantity and volume of spare parts. The analysis was conducted using a 5S checklist, assessment of existing conditions, implementation of the 5S method, and evaluation after improvements. The results showed an increase in the score from 18 to 74, indicating a more organized, neat, clean, and disciplined workplace. This improvement was supported by the establishment of SOPs, which include sorting, organizing, cleaning, utilization, and maintenance of workshop equipment.